Wasiat Wajibah dalam Sistem Kewarisan Islam di Indonesia: Studi Kasus Yurisprudensi dan Implikasinya bagi Ahli Waris Non-Muslim - Fauzan, Rafli Akmal; Amalia, Lia; Abas, Muhamad (Universitas Widya Gama Malang, 2025)
This article aims to analyze the regulations regarding compulsory bequests (wasiat wajibah) in the Islamic inheritance system in Indonesia, particularly concerning non-Muslim heirs. The primary focus is to understand how Indonesian jurisprudence and regulations respond to and accommodate the inheritance rights of heirs of different religions. The methodology used in this research is a normative juridical approach, encompassing legislative analysis, case law, and examination of legal documents such as the Compilation of Islamic Law (KHI) and Supreme Court decisions. The findings reveal that although traditional Islamic legal sources like the Quran, Sunnah, Ijma, and Qiyas have not yet accommodated compulsory bequests for non-Muslim heirs, the development of Indonesian jurisprudence has begun to recognize these rights. Supreme Court rulings, such as Decision Number 368 K/Ag/1995 and Number 51 K/Ag/1999, have paved the way for the acknowledgment of compulsory bequests to non-Muslim heirs. These decisions indicate the judges' efforts to balance justice and equality in a pluralistic society. The regulation of compulsory bequests in Indonesia has experienced significant development by including non-Muslim heirs in the inheritance scheme through compulsory bequests. This reflects the adaptation of Islamic law to the evolving social context and demonstrates the commitment of Indonesian judicial institutions to interpreting the law in a more inclusive and equitable manner. This jurisprudence is crucial for providing justice to all parties, regardless of religious differences, and showcases the flexibility of Islamic law in addressing contemporary societal needs.